SISTEM INFORMASI ADMINISTRASI PENGGAJIAN GURU PADA SD MADANI CILEGON-BANTEN - Darpi Darpi; Sawitri Nurhayati; Khasan Asrori (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
So far, SD Madani Cilegon still uses Ms. Excel in the payroll administration process, the data is not stored in the right place so it is difficult to disburse the data is very less effective and efficient. In addition, reports are still in the form of piles of paper and are not grouped together, so the process of making them is complicated. This study aims to design a more structured and computerized payroll information system at SD Madani Cilegon. The research method used in this study is the waterfall method. When designing using Data Flow Diagram (DFD)design tools, Entity Relationship Diagram (ERD), file specifications, HIPO, and interface design. For the implementation using Visual Basic 6.0 and Microsoft Access 2010 database. The results of this study resulted in a payroll administration information system at SD Madani Cilegon. It is hoped that with the payroll administration system at SD Madani Cilegon it can be processed more effectively administratively, there are no payroll errors and the reporting process is fast. Keywords: Information System, Payroll Administration, Waterfall Method